On the meaning of Feifa Quanyi in Chinese legal language: A semiotic and corpus analysis. Issue Volume 12:(2016)Special Issue (26th July 2018) - Mannoni, Michele; Cao, Deborah
Abstract : 'Illegal rights' is an oxymoron in many European languages, including English. A new term feifa quanyi (illegal rights and interests) has appeared in recent times and is now being used increasingly in court decisions and litigation in China. In this study we use a semiotic and corpus-based approach to examine the Chinese legal texts and court decisions containing the phrase to ascertain the meanings of the phrase. The various implications of the analysis of this unique new legal usage are discussed in terms of the study of Chinese legal language with semiotic and corpus analysis.